A Review on Composite Papers of Graphene Oxide, Carbon Nanotube, Polymer/GO, and Polymer/CNT: Processing Strategies, Properties, and Relevance. (12th April 2016) - Khan, Zaheen Ullah; Kausar, Ayesha; Ullah, Hidayat
ABSTRACT: In this review, particular importance is given to the fabrication and properties of carbon nanotube and graphene oxide-based paper-like materials (buckypapers). Different strategies for the reduction and functionalization of graphene oxide were also discussed. The chemistry of buckypapers is conversed with special emphasis on structure and essential characteristics of buckypaper. Various techniques for buckypaper processing have been critically reviewed including significance of each method. Moreover, importance of polymer/graphene oxide and polymer/carbon nanotube composite papers has been highlighted. Due to outstanding physical, thermal, and electrical properties, polymer-based buckypapers are potentially important as nanofilters, fuel cell components, and miniaturization of electrical connections. GRAPHICAL ABSTRACT: